Integrasi Nilai Islam Dalam Pendidikan: Pembelajaran Integratif di SMA Islam Al-Muttaqin Kota Tasikmalaya - Syarip Hidayat (State Islamic Institute of Madura, 2021)
Various forms of negative impacts contained in the modernization and globalization are becoming seious challenges for education. Moral decadence in the form of negative behaviors, such as the use of drugs, free sexual, and brawling, are the impacts of the presence of modernization and globalization. These social reality with negative values requires to reform patterns of education. One form of the intended redesigning is by integrating Islamic values. This research is qualitative with descriptive method. The data analysis technique uses triangulation and interpretation. The focus of the research are (1) The values of Islam which is integrated in learning; (2) The integration form of Islamic values in education; (3) Constraints faced when integrating Islamic values in learning; (4) Efforts to overcome obstacles in the integration of Islamic values. After conducting of interpretation of research data, there are several conclusions. (1) The values that are integrated in learning, which are in the form of practical and applicative values, are the instrumental values where every value is responsible for keeping the students’ dignity as Allah’s creature such as perseverance, discipline, honesty, patience, togetherness, and cleanliness. (2) The integration of Islamic values is applied in the implementation of integrative islamic education in the whole scope of education. (3) The obstacles found in the integration process are more dominant on uniting the perspectives of relation between Islamic values and practical importance of education. (4) Efforts to overcome the constraints of the integration are done through persuasive approach and examplary.